ANALISIS HUBUNGAN KEPEMIMPINAN GURU DAN MINAT BELAJAR SISWA PADA MATA PELAJARAN FIKIH DI MTS MALNU MENES PANDEGLANG - Jamil, Moh.; Masroni, Masroni (STIT AL-AMIN KREO TANGERANG, 2024)
This study aims to determine the effect of teacher leadership on students' interest in learning Fiqh at MTs MALNU Menes Pandeglang. The study used a correlational method, with a sample of 34 students taken from a population of 114 students through the Proportionate Stratified Random Sampling technique. Data were collected through questionnaires and processed using descriptive analysis and correlation tests. The results showed that teacher leadership has a significant influence on students' interest in learning Fiqh. Based on the results of the regression analysis, the correlation coefficient between the variables of teacher leadership (X) and student interest (Y) is 0.64. This indicates a moderate positive correlation, where 40.96% of the variation in student interest can be explained by teacher leadership, while 59.04% is influenced by other factors not examined in this study. The level of teacher leadership is in the very good category with an average achievement level of 84.78%, while student interest is classified as good with an achievement level of 80.16%